Malignant Melanoma of Oesophagus: A Rare Entity - Mohamed Arif Bin Hameed Sultan; Nik Ritza Kosai; Reynu Rajan; Mustafa Taher; Aznan Shuhaili; Dayang Corieza Febriany (Gazi University, 2022)
We are discussing a case of malignant melanoma of esophagus, initially presented to us with very atypical presentation. On further history, patient claim having dysphagia for few months, initially to solid then followed by liquid, progressively worsening over few months. On further examination, OGDS reveal pedunculated growth at 30cm and 32 cm with skip free intact mucosa in between. Subsequently, we optimize his nutritional status and performed open tranhiatal total esophagectomy with cervical anastomosis and feeding jejunostomy. Post-operative recovery was uneventful, and patient was well upon discharge. Histopathology of the specimen revealed malignant melanoma of the esophagus. On subsequent follow up. PET scan was also done and shows stable disease with no evidence of tumor recurrence